Systemic Lupus Erythematosus with Severe Renal Dysfunction and Severe Hematological Manifestation Lead to Septic Shock: A Case Report - I Nyoman Suarjana; Ayu Cahya Andhayani (Indonesian Journal of Rheumatology, 2020)
Abstract: Background:Systemic Lupus Erythematous (SLE) is an autoimmune disease that can cause major mortality and morbidity if untreated well. Various clinical manifestations and adverse events may affect the patient condition. Case Report: We reported a case of a 31 years old female patient with systemic lupus erythematosus who presented with lupus nephritis and a hematological manifestation lead to septic condition and septic shock. This is a case where initially the patient is well controlled for 1.5 years but due to 6 months of absence treatment, the SLE flareupand she suffers an end-stage renal disease(ESRD). This patient was treated with mycophenolate acid in combination with high dose steroids, antibiotics, granulocyte-colonystimulating factor and underwent hemodialysis. Because of the ESRD and a manifestation of severe neutropenia and lymphopenia, the patient experienced urinary tract infection. She suffered from severe septic with shock condition and passed away later on. Conclusion:A SLE patient with a severe manifestation of neutropenia and lymphopenia accompanied with end-stage renal failure can cause an opportunistic infection that leads to severe septic shock condition and multi-organ failure. Keyword:Systemic lupus erythematosus, lupus nephritis, hematological manifestations, septic shock, Case Report